PENERAPAN NILAI-NILAI TRADISI WUAT WA’I DALAM TERANG GRAVISSIMUM EDUCATIONIS TENTANG PENDIDIKAN LANJUTAN ANAK KE PERGURUAN TINGGI PADA MASYARAKAT MBAPO KABUPATEN MANGGARAI TIMUR - Bele, Graciana A.; Siono, Yeremias; Mbaling, Graciana (Pastoralia Jurnal Penelitian Dosen, 2022)
The Wuat Wa'i tradition is one of the traditions of the East Manggarai community which aims to support regional children who want to continue their education at university. This tradition is better known as "children's school party". This habit is closely attached to the Mbapo community and is a good tradition because the people realize that it costs a lot of money to send children to a higher level of education. However, if we look at the realities of today's developments, this tradition is not well understood by young people. This tradition is used as a place to have fun and have fun without interpreting it properly. The focus of this research is to examine the noble values ​​found in the Wuat Wa'i tradition and relate them to the teachings of the Gravissimus Educationis Catholic Church which talks about education. The method used in this research is descriptive qualitative. From the results of interviews with 7 informants, the author can conclude that the Mbapo community has a good understanding of the meaning of education for their children, even though their lives are simple and deficient, they still help and support each other so that their children can continue their studies at university level. tall. The noble values ​​contained in this tradition are a sense of brotherhood, togetherness, mutual support and help, mutual cooperation and making the Wuat Wa'i tradition a custom to help humanize humans.